Melatonin in animal husbandry: functions and applications - Zhao, Ruohan; Bai, Yicheng; Yang, Fangxiao (Frontiers in Veterinary Science, 2024)
Melatonin (N-acetyl-5-methoxytryptamine) is an essential small molecule with diverse biological functions. It plays several key roles, including regulating the secretion of reproductive hormones and the reproductive cycle, enhancing the functionality of reproductive organs, improving the quality of sperm and eggs, and mitigating oxidative stress in the reproductive system. Melatonin effectively inhibits and scavenges excess free radicals while activating the antioxidant enzyme system and reduces the production of inflammatory factors and alleviates tissue damage caused by inflammation by regulating inflammatory pathways. Additionally, melatonin contributes to repairing the intestinal barrier and regulating the gut microbiota, thereby reducing bacterial and toxin permeation. The use of melatonin as an endogenous hormone in animal husbandry has garnered considerable attention because of its positive effects on animal production performance, reproductive outcomes, stress adaptation, disease treatment, and environmental sustainability. This review explores the characteristics and biological functions of melatonin, along with its current applications in animal production. Our findings may serve as a reference for the use of melatonin in animal farming and future developmental directions.